Pengembangan Video Animasi Sebagai Media Pembelajaran Praktis - Wayan Mahardika Prasetya Wiratama (Universitas Pendidikan Ganesha, 2023)
This study aimed to create and develop a learning media in an animated video of a 3-phase electric motor control circuit for the Electric Motors Course at Undiksha Electrical Engineering Education S1 Study Program. This research followed the research and development method. This study used statistical analysis techniques percentages to process the data from content experts, media experts,and testing on students. This study found that the content expert validation test result is 90.9%, with avery decent qualification. The media expert validation test is 96.42%, with a very decent qualification. Small group trials of 6 respondents and large group trials of 20 respondents confirm that the product has a very high qualification. The learning media in the form of an animated video of the movement of electric current in a 3-phase electric motor controller circuit is suitable for use in the Electric Motor course learning process in the Undiksha Electrical Engineering Education Study Program.